Attachment and Isolation: Exploring Kya's Relationships in Delia Owens' Where the Crawdads Sing - Tuomikoski, Sanni (My University, 2025)
In this thesis I examine the influence of childhood abandonment and isolation on the protagonist Kya Clark’s attachment style and relationships in Delia Owens’ Where the Crawdads Sing (2018). By analysing Kya’s interactions with Tate Walker and Chase Andrews through the lens of attachment theory, I delve into how her avoidant attachment style shapes her romantic relationships and social connections. I aim to explore Kya’s fear of intimacy, longing for connection and self-reliance, and the way that these aspects contribute to her navigation of romantic relationships. Additionally, I explore the societal prejudice Kya faces from a society that has continually rejected her and how it is particularly evident during Chase Andrews’ murder trial, which also serves as a culmination of her struggles with isolation, abandonment. Ultimately, I argue that isolation and attachment style significantly influence an individual’s ability to form and navigate relationships throughout their life.
Keywords: attachment theory, avoidant attachment, isolation